2023
DOI: 10.3389/fimmu.2022.1075423
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and T-cell response 12 months after the first BNT162b2 vaccination in solid organ transplant recipients and controls: Kinetics, associated factors, and role of SARS-CoV-2 infection

Abstract: IntroductionWe investigated humoral and T-cell responses within 12 months after first BNT162b2 vaccine in solid organ transplant (SOT) recipients and controls who had received at least three vaccine doses. Furthermore, we compared the immune response in participants with and without previous SARS-CoV-2 infection.MethodsWe included adult liver, lung, and kidney transplant recipients, and controls were selected from a parallel cohort of healthcare workers.ResultsAt 12th-month, the IgG geometric mean concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 76 publications
3
11
0
Order By: Relevance
“…As SARS-CoV-2 variants continue to evolve, understanding vaccine immunogenicity in vulnerable populations is critical to informing vaccination strategies. SOTRs show impaired humoral and cellular responses to mRNA vaccines, 5,9,29,49 corresponding with increased susceptibility to SARS-CoV-2 infection. 4,25 In the present study, we have provided the first AIM-based characterization of COVID-19 vaccine-induced T cell responses to BA.4/5 and XBB.1.5 in SOTRs.…”
Section: Discussionmentioning
confidence: 99%
“…As SARS-CoV-2 variants continue to evolve, understanding vaccine immunogenicity in vulnerable populations is critical to informing vaccination strategies. SOTRs show impaired humoral and cellular responses to mRNA vaccines, 5,9,29,49 corresponding with increased susceptibility to SARS-CoV-2 infection. 4,25 In the present study, we have provided the first AIM-based characterization of COVID-19 vaccine-induced T cell responses to BA.4/5 and XBB.1.5 in SOTRs.…”
Section: Discussionmentioning
confidence: 99%
“…As SARS-CoV-2 variants continue to evolve, understanding vaccine immunogenicity in vulnerable populations is critical to informing vaccination strategies. SOTRs show impaired humoral and cellular responses to mRNA vaccines 5,9,28,30 , corresponding with increased susceptibility to infection 4,25 . In the present study, we have provided the first AIM basedcharacterization of COVID-19 vaccine-induced T cell responses in SOTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination also induces comparatively weaker Spike-specific IFN-γ+ and/or IL-2+ T cell responses than natural infection in SOTRs 29,30 .…”
Section: Covid-19 Vaccines Effectively Reduce Infections Hospitalizat...mentioning
confidence: 98%
“…Studies presenting results from flow cytometric analysis demonstrated pooled response rates of 16.1% (95%CI 8.5-25.4%) after the first dose, 73.7% (95%CI 55.2-88.8%; I 2 85.6%) after the second dose, and 86.5% (95%CI 75.3-94.9%; I 2 70.1%) after a third booster dose (Figure 2C). Only six studies included recipients with previous SARS-CoV-2 infection (27,29,30,37,41,45). Supplementary Figure S1 illustrates the cellular immune response rate after excluding the results from these studies, and the results were not different from the primary analyses that included recipients with previous SARS-CoV-2 infection.…”
Section: Cellular Immune Response After Sars-cov-2 Vaccination In Kid...mentioning
confidence: 99%